Characterisation of wellbore cement microstructure alteration under geologic carbon storage using X-ray computed micro-tomography: A framework for fast CT image registration and carbonate shell morphology quantification. (April 2020) - Miao, Xiuxiu; Zhang, Liwei; Wang, Yan; Wang, Lun; Fu, Xiaojuan; Gan, Manguang; Li, Xiaochun
Abstract: An aqueous CO2 –cement interaction experiment along with X-ray computed micro-tomography characterisation of pre- and post-exposure cement samples was carried out to investigate the cement structure evolution under geologic carbon storage conditions. An image processing framework was proposed for mapping mineral dissolution and precipitation and characterisation of carbonate shell morphology. The main workflow covered in this framework is to, 1) register cement CT images before and after reaction; 2) generate the difference image showing chemical alteration and map the difference image to demonstrate local content changes of pore space, calcite and portlandite; 3) segment carbonate shell from the difference image; 4) generate auxiliary images including skeleton, 3D local thickness and surface boundaries of the carbonate region, and 5) spatial quantification of the area, thickness, penetration depth and pore/calcite/portlandite content changes of the carbonate shell. The effectiveness of the framework was validated through step-by-step demonstration of results when deploying the framework to process the CT images of six cement samples acquired before and after reaction with CO2 . The 3D mineral precipitation and dissolution (or local mineral content change) map and the internal and external carbonate shells were visualised. The spatial distribution of the shell area, thickness, penetration depth and pore/calcite/portlandite content changes along the height of the sample was revealed. Overall, the dissolution and precipitation map gives more intuitive and interpretable results of CO2 -induced chemical alteration than direct visual comparison from the original CT images, and the morphological quantification of the carbonate shell gives reasonable interpretation of the spatial distribution of the carbonate reaction.